The effect of COVID-19 towards energy sector in Malaysia stock market / Nabilah Afiqah Noor Iskandar - Noor Iskandar, Nabilah Afiqah (2022)
Covid- 19 has spread over the world since the first case was discovered at the end of 2019 that is resulting in over 2 million confirmed cases. On I Ith March 2020, the World Health Organization (WHO) declared the Covid-19 disease a pandemic. The Covid-19 outbreak has also had an influence on the global financial industry including Malaysia. The influence of the Covid19 outbreak on the Malaysia stock market's energy industry is investigated in this study. The investigation also revealed that there were a few events that had an influence on the Malaysia stock market during the Covid-19 pandemic. The number ofCovid-19 daily cases (COVC), the number of Covid-19 daily death cases (COVD) and the Chicago Board of Exchange (CBOE) VIX index were used as independent variables. The study's sample period was from 4th January 2021 to 31st December 2021. According to the research, the COVD showed a negative relationship with the energy sector performance in the Malaysia stock market with the number of Covid-19 daily cases being virtually significantly influenced by the number of Covid-19 daily cases. The COVC has a strong relationship with the energy industry. Number of daily cases in Malaysia not boosted the performance of the sectorial index. As a result, a few crucial conclusions are established. While the number of new Covid-19 cases had no influence on daily deaths, it had a significant impact on the energy and index returns. Furthermore, this analysis can help market participants understand how the Malaysia stock market performed during Covid- 19.